2023
DOI: 10.1007/s11096-023-01626-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, contributing factors, and interventions to reduce medication errors in outpatient and ambulatory settings: a systematic review

Lina Naseralallah,
Derek Stewart,
Malcom Price
et al.

Abstract: Background Medication errors are common events that compromise patient safety. Outpatient and ambulatory settings enhance access to healthcare which has been linked to favorable outcomes. While medication errors have been extensively researched in inpatient settings, there is dearth of literature from outpatient settings. Aim To synthesize the peer-reviewed literature on the prevalence, nature, contributory factors, and interventions to minimize medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Pharmacists can also play a vital role by identifying medication errors which will help in better outcomes. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists can also play a vital role by identifying medication errors which will help in better outcomes. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, discrepancies in discharge summaries are common in Sweden and the rest of the world. Studies have found significant error rates: up to 87% of discharged patients are affected [ 1 , 10 17 ]. Thus, ensuring a Correct-ML at discharge is necessary.…”
Section: Introductionmentioning
confidence: 99%